Knowing What Justice Means and Being Committed to It: Remarks on Allen Buchanan's Analysis of Conservative Factual Beliefs. Issue 5 (22nd December 2021) - Forst, Rainer
ABSTRACT: Allen Buchanan argues that a particular set of false factual beliefs, especially when part of a comprehensive ideology, can lead persons to develop 'morally conservative' convictions that stand in the way of realising justice even though these persons have a 'firm grasp of correct principles of justice and a robust commitment to their realisation'. In my remarks, I raise some questions concerning the core argument: How 'firm' can a grasp of principles of justice be if a person is blind to the realities of injustice? And how 'sincerely committed' to justice can such an injustice‐insensitive person be? Alternatively: How firm is that grasp or commitment if one has a radically pessimistic view about human nature so that one does not believe that (egalitarian) justice can or could ever be realised? Secondly, I ask: If such ideologies or false beliefs are in play in reproducing injustice, do they not also 'mask' existing injustices?